1000FARMS Platform Annual Meeting Report 2023 - Bioversity International; International Center for Tropical Agriculture (2023)
The 1000FARMS Platform aims to establish an Africa-wide network for on-farm testing. The project started in late 2021 and is funded by the Bill & Melinda Gates Foundation (BMGF) and implementation is done in partnership between the Alliance of Bioversity International and CIAT (project lead), IITA, CIMMYT, INN University (until 2023), and Wageningen University. 1000FARMS works intensively with CGIAR-NARES breeding networks through other CGIAR-led projects.